Master Training of Translation Specialists in the Context of the Postmodern Educational Paradigm. - Testsova, O.; Dudina, O.; Holovko, I.; Тецова, О.; Дудіна, О.; Головко, І. (LUMEN Publishing, 2022)
The article deals with the problems of inconsistency of Ukrainian translation education with the trends of the postmodern state of society and the advisability of introducing the achievements of the American system of training translators is substantiated. Thearticle describes the organization of training masters in technical translation in the United States on the basis of a systematic analysis, in particular, the structure and content, forms and methods of teaching and learning masters in technical translation. Postmodern tendencies and peculiarities of master's education in the USA are revealed and substantiated. The principles of permanent improvement of translation competence, profile and general cultural orientation are described; ensuring the full formation of the readiness of graduates of master's programs in technical translation for highly qualified, productive and creative professional activities; learning in a multicultural environment; application of the latest means of automated translation during training; certification of technical translators. For the reform of translation education in Ukraine, these trends are identified as key. The results of the study were obtained by applying a comparative typological and systems analysis, the method of extrapolating educational trends in the United States and Ukraine in relation to the postmodern context of society and its practical requirements for translation education. The practical significance of the article lies in borrowing the American experience of postmodern aspects of translation education, which can be useful to the countries of the former socialist camp and post-Soviet society.
Магістерська підготовка перекладачів у контексті постмодерної освітньої парадигми
Keywords: professional training; postcolonial education; technical translation; US universities; master's programs; multicultural environment